An application of advanced oxidation process to photopolish palm oil mill effluent over TIO2 and ZnO photocatalysts - Ng, Kim Hoong (2017)
The reactivity of both UV/TiO2 and UV/ZnO systems in treating palm oil mill effluent (POME) were investigated in current study. XRD revealed that TiO2 and ZnO, with the band gap energy of 3.15 and 3.20 eV respectively, were free from impurities. ZnO photocatalyst has irregular shape, bigger in particle size but lower BET specific surface area (9.71 m2/g) compared to the spherical TiO2 photocatalysts (11.34 m2/g). The degradation process of POME was conducted in a 500 mL Pyrex photoreactor at room temperature with the irradiation of 100 W UV lamp. With 1.0 g/L of photocatalyst and 70 mL/min of O2 bubbling, the degradation obtained by UV/TiO2 system (52.0%) is slightly higher compared to UV/ZnO system (50.0%) in 240 min of UV irradiation and the performance gap between two systems was broaden after 22 h of UV irradiation. At the end of the experiments, the degradation achieved were 80.35% and 74.11% for UV/TiO2 and UV/ZnO system, respectively. Nonetheless, the final COD, BOD and oil and grease (O&G) level of POME for UV/TiO2 system (33, 16, and 10 ppm) and UV/ZnO system (44, 26, and 20 ppm) were successfully brought down to the safe level for discharging. In recyclability test, TiO2 exhibits a higher stability, as no significant deactivation was observed after three consecutive cycle of photoreaction, compared to 24.0% of deactivation in UV/ZnO system. Scavenging test reveals that the main reactive species for POME degradation for both systems are different. OH• free radical decomposed most organics in UV/TiO2 while UV/ZnO system generates OHads• for most of the organic degradation. The ability of organic-adsorption in ZnO photocatalyst allows the degradation process occurs on its surface. For TiO2 photocatalyst, the organic degradation can only happen in bulk solution due to the poor affinity of TiO2 towards organic pollutants. This is further supported by the post-reaction analysis conducted on spent photocatalysts both systems, confirming the carbonaceous species only detected on the surface of ZnO. 23 full factorial design in Response Surface Methodology (RSM) was employed and confirmed that O2 flowrate, photocatalyst loadings and initial concentration of POME are significant in both system. Furthermore, it also confirmed the existence of interactive factors in both systems. Subsequently, all three main factors for both systems were optimized by using Central Composite Design (CCD) in RSM. Quadratic models with high R2 values (>0.9) and excellent residue analysis were developed for both systems to describe the degradation. The optimized conditions were suggested and experiments (duplicated) were conducted for both system. Based on the results obtained, the degradation of UV/TiO2 system were successfully optimized to averaged degradation of 55.0% after 240 min of UV irradiation in the presence of 1.04 g/L of TiO2, 66.0 mL/min of O2 bubbling and initial POME concentration of 240 ppm. On the other hand, the degradations of UV/ZnO system were optimized to averaged degradation of 55.29%, with 60 mL/min of O2 bubbling, 1.26 g/L of ZnO and 220 ppm of POME, after 240 min of UV irradiation. The errors between the estimated and experimental degradation recorded for UV/TiO2 system and UV/ZnO system were very low (4.41 and 5.40%, respectively), hence confirming the adequacy of the models developed.